AB104. The expression and function of coiled-coil domain-containing protein 34 in human bladder carcinoma - Gong, Yanqing (Transl Androl Urol, 2016)
OBJECTIVE: The coiled-coil is a superhelical structural protein motif involved in a diverse array of biological functions, and the abnormal expression of the coiled-coil domain containing proteins has a direct link with the phenotype of tumor cell migration, invasion and metastasis. Here, we first reported the oncogenic roles of coiled-coil domain-containing protein 34 (CCDC34), and investigated its biological functions in bladder carcinogenesis. METHODS: Immunohistochemical staining, western blot and quantitative RT-PCR were used to detect CCDC34 expression in bladder cancers specimens and cell lines. Lentivirus-mediated RNA interference strategy was used to assess the effects of CCDC34 expression on various malignant phenotypes. The biological functions of CCDC34 knockdown on cells (T24 and 5637) were investigated by examining cell proliferation using a high content screening assay (HCS), BrdU incorporation assay and colony formation assay, cell migration by in vitro wound healing assay, cell invasion by Transwell invasion assay, as well as cell cycle distribution and apoptosis by flow cytometry. The expressions of c-Raf and c-Jun as well as the phosphorylation of MEK, ERK1/2, JNK, P38 and AKT were also measured using Western blot. We further investigated the effect of therapeutic siRNA targeting CCDC34 on T24 xenograft tumor growth in nude mice. RESULTS: CCDC34 was up-regulated in human bladder cancer tissues and cell lines. CCDC34 was distributed mainly in the cytoplasm, and its expression was not correlated with gender, histological type and tumor grade, but was closely correlated with pathologic stage (n=87, P<0.05). Besides, Western blot confirmed that CCDC34 was expressed at higher level in human bladder cancer tissues compared with their paraneoplastic normal bladder tissues (n=18, P=0.012). Knockdown of CCDC34 significantly suppressed bladder cancer cells proliferation, migration and invasion (P<0.01), and induced cell cycle arrest at G2/M phase and increased apoptosis in vitro (P<0.01). Moreover, CCDC34 knockdown decreased phosphorylation of MEK, ERK1/2, JNK, p38 and AKT, and the expressions of c-Raf, c-Jun and Bcl-2. In addition, intratumor delivery of therapeutic siRNA targeting CCDC34 elicited delayed tumor growth of T24 xenograft in nude mice. CONCLUSIONS: Our findings revealed for the first time a potential oncogenic role for CCDC34 in bladder carcinoma pathogenesis, and the MAPK and AKT signaling pathways might be involved in CCDC34 modulation of bladder cancer cell proliferation, migration and invasion. CCDC34 may serve as a biomarker or even a therapeutic target for bladder cancer.